Recovery of α-Al2O3 from Ionizing Radiation Dosimetric Sensors - Sanches,Edgar Aparecido (2015)
Corundum, sapphire or α-Al2O3 is an important technological material in many optical and electronic applications such as solid-state lasers, optical windows and, more recently, as a radiation detector. Landauer (Glenwood, IL, USA) accumulated large number of archived and stored Luxel™ dosemeters composed of Al2O3:C, which were subjected to a recovery process. Due to the importance of this advanced crystalline material in OSL dosimetry, a recovery process was developed based on the dosemeters calcination and Al2O3:C has been reused in manufacturing of new dosemeters. This paper does not aim to optimize the recovery process, but provides an opportunity to study the involved process parameters and to recover this valuable crystalline material from used dosemeters. To the best of our knowledge no other recovery process involving this dosimetric material was described in scientific literature. Fourier Transform Infrared Spectrometry (FTIR), Thermogravimetry/Differential Thermoanalysis (TG/DTA), Differential Scanning Calorimetry (DSC), X-ray Diffraction (XRD), Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES), Optically Stimulated Luminescence (OSL) and Rietveld Refinement were used to characterize the recovered material and to check for the stability of its structural and dosimetric properties.